Maackia amurensis agglutinin induces apoptosis in cultured drug resistant human non-small cell lung cancer cells - Chhetra Lalli, Rakhee; Kaur, Kiranjeet; Chakraborti, Anuradha; Srinivasan, Radhika; Ghosh, Sujata (Glycoconjugate journal, 2019)
The emergence of multi drug resistance in non-small cell lung cancer (NSCLC) patients is a major challenge towards the efficacy of chemotherapy. Thus, there is an urgent need for the newer, better clinically targeted strategies to treat this disease. Earlier studies from our laboratory revealed the apoptotic activity of Maackia amurensis agglutinin (MAA) in human NSCLC cells. In this study, the effect of MAA on drug resistant NSCLC cells was investigated. Two Paclitaxel-resistant NSCLC sub-lines (A549/PTX100 and NCI-H460/PTX100) were developed from A549 & NCI-H460 cell lines respectively. The generation of drug resistance phenotype was confirmed by the expression of cell surface MDR-1. Both the drug resistant sub-lines showed distinct morphological alterations. MAA interacted with the cell-surface protein(s) of apparent M r ~66 kDa and induced apoptosis in both the sub-lines through intrinsic/mitochondrial pathway, involving reduction in mitochondrial trans-membrane potential, up-regulation of Bax, unaltered/decreased expression of Bcl-X L , release of mitochondrial cytochrome c into the cytosol and activation of pro-caspases (−9&-3). Our findings highlighted the potential of this plant agglutinin to serve as an apoptosis inducing agent in drug resistant NSCLC cells.